Creación de un plan estratégico publicitario mediante el método AIDA para el posicionamiento de la microempresa Provetal Campo en medios digitales y tradicionales - Guamán Cargua, Omar David (2024)
The objective of this research work was to create a strategic advertising plan based on the AIDA method to improve the positioning of Provetal field in digital and traditional media. For this purpose, the AIDA methodology was used, whose stages are based on attention, which is based on attracting attention with attractive techniques so that the consumer notices the product; Interest: capturing interest by providing relevant information and benefits; Desire: transforming interest into desire; in this way, the consumer is guided to take a concrete action such as purchasing a product or service. Thus, most of the surveyed customers of “Provetal field” indicated their preference for using social networks such as Facebook, Instagram, WhatsApp, and TikTok as means of communication and direct information. It was also noticed that printed media are still present since a certain percentage of people do not have access to the internet or technological resources or due to a lack of knowledge of their use. These results responded to the notorious need for Provetal field to implement a multichannel communication strategy due to its lack of dissemination of its products and services in digital and print media in an adequate manner. Even so, it was concluded, according to the matrix of communication effectiveness, that the communication problem used by the microenterprise is located in the lack of implementation, both traditional and digital media, so it has not had the scope and adequate reception in recent years. Therefore, a strategic advertising plan was created, which contributed to improving the positioning, recognition, and image of “Provetal field,” capturing the attention of its customers and potential customers in the future through the use of traditional media and digital media such as social networks. It is recommended that an expert in the area of graphic design be hired to properly apply the appropriate standards and fundamentals, as well as invest in the physical materialization of the proposals designed in this research.